Scientist Online: Entomologists' Experiences Engaging With School Audiences Through Skype in the Classroom - Krebs, Christine L.; Loizzo, Jamie L.; Stone, Whitney A.; Telg, Ricky W. (Frontiers in Communication, 2020)
Scientists often aim to inspire others who may not be as knowledgeable about specific scientific concepts to increase science interest and knowledge, mobilize communities for social and political change, and encourage the pursuit of STEM careers. Ideally, scientists would interact with public audiences face-to-face for rich dialogue and engagement at community venues such as libraries, churches, schools, and grocery stores. However, research shows the majority of Americans spend their time searching for scientific information on the web. As an alternative, some scientists have taken to participating in produced online video. Some online video platforms allow for synchronous dialogic engagement, such as Skype, for video-sharing. Skype in the Classroom is offered for school interactions with content experts through virtual field trips. The following study provides a practical overview of a specific program called ‘Scientist Online: The Science of Mosquitoes,’ its application of Skype in the Classroom two-way video technology for fostering STEM dialogue, and a qualitative analysis of scientists’ experiences and scientist-student interactions. The authors analyzed interviews with the participating scientists and call transcriptions of the scientist-student conversations with five schools and more than 100 students from Florida, Pennsylvania, Canada, and Pakistan.  Skype in the Classroom served as an effective platform for scientists to engage with various school audiences, improving their confidence in science communication. The online synchronous format of Skype in the Classroom prompted scientists to prepare content and conduct background research of participants’ locations in advance. Scientists recognized the importance of their roles as science communicators to dialogue about science in digestible terms, and Skype in the Classroom allowed them to balance their roles as researchers and contributors to public outreach. Recommendations are also discussed.